Pendidikan Anak Usia Dini dalam Perspektif Islam: Early Childhood Education in Islamic Perspective - Mahrus Mahrus (Fenomena, 2012)
Education is a continuing process of the students’ body and soul development. A teacher needs to understand the children’s development to achieve educational purposes optimally. Islam divides children's development into two periods: the prenatal period and the after-natal period. This research focuses on the after-natal period, with the results being descriptive data analyzed using a qualitative approach. The findings indicate that human beings possess a fitrah (innate nature) that needs to be developed, including the fitrah of faith in Allah, the willingness to accept goodness and education, curiosity about the truth, biological desires in the form of syahwat and ghadlab (instinct), and other potentials inherent in every individual. Pendidikan merupakan proses berkelanjutan dalam pengembangan jasmani dan rohani anak didik. Seorang pendidik perlu memahami perkembangan anak agar dapat mencapai tujuan pendidikan secara optimal. Islam membagi periode perkembangan anak menjadi dua, yaitu periode sebelum kelahiran (prenatal) dan setelah kelahiran (after-natal). Penelitian ini berfokus pada periode setelah kelahiran dengan hasil berupa data deskriptif yang dianalisis menggunakan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa manusia memiliki fitrah yang perlu dikembangkan, meliputi fitrah keimanan kepada Allah, kesediaan menerima kebaikan dan pendidikan, rasa ingin tahu terhadap kebenaran, dorongan biologis berupa syahwat dan ghadlab (insting), serta potensi lain yang dimiliki setiap manusia.